Social behavior of proterotheriid ungulates revealed by mammal tracksites in northwest Argentina - Vera, Rocío Belén (2025)
Two Late Miocene tracksites in Argentina—Toro Negro and Huayquerías formations—preserve over 300 fossil footprints, offering new ichnological insights into the behavior of extinct South American ungulates. These sites include abundant oval-shaped tracks attributed to proterotheriids, a monodactyl group within Litopterna that evolved horse-like limbs. We describe Okana andina n. igen. n. isp., characterized by elongated, anteriorly narrow tracks lacking lateral digit impressions. Detailed analysis of track morphology, preservation, spatial distribution, and footprint orientation reveals patterns consistent with coordinated group movement. To test this behavioral inference, we evaluated multiple hypotheses for the formation of these high-density surfaces, including non-synchronous accumulation, ephemeral aggregation around localized resources, spatial channeling by environmental barriers, and selective preservation bias. These alternatives were rejected based on the ichnological and sedimentological context, including uniform preservation type, consistent morphology, directional coherence, and analogy with modern gregarious ungulates. The evidence supports near-synchronous movement by multiple individuals, providing the first ichnological record of social behavior in Proterotheriidae and expanding our understanding of group-living in extinct South American native ungulates.